Using subject headings for online retrieval theory, practice, and potential - Vizine-Goetz, Diane; OCLC. (San Diego, Calif. : Academic Press, 1994)
Using Subject Headings for Online Retrieval is an indispensable tool for online system designers who are grappling with developing new systems or refining existing ones. This ready reference describes subject analysis and subject searching in online catalogs, including the limitations of retrieval, and demonstrates how such limitations can be overcome through system design and programming. The practical reference also describes the Library of Congress Subject Headings (LCSH) system and system characteristics; it shows how information is stored in machine-readable files; and it offers examples of and recommendations for successful retrieval methods. Tables are included to support these recommendations, and diagrams, graphs, and bar charts are used to provide results of data analysis. Practitioners in institutions using or considering the installation of an online catalog will continuously consult this book to generate specifications. The book also appeals to researchers in library systems, information retrieval, and user behavior because it details the results of an extensive, empirical study of the subject terms entered into online systems by end users. It also addresses the needs of advanced students in library schools and instructors in library automation, information retrieval, cataloging, indexing, and user behavior. It overviews the LCSH system and system characteristics. It describes how information is stored in machine-readable files. It offers examples of and recommendations for successful retrieval methods. Empirical evidence supports recommendations.
Subject analysis in library catalogs / Diane Vizine-Goetz -- Subject heading compatibility between LCSH-mr and bibliographic files / Diane Vizine-Goetz -- Studies of the subject queries users enter into online systems / Diane Vizine-Goetz -- An overview of user queries / Diane Vizine-Goetz -- Queries for topical subjects that are likely to succeed / Diane Vizine-Goetz -- Other queries likely to succeed / Diane Vizine-Goetz -- Queries for topical subjects not likely to succeed / Diane Vizine-Goetz -- Other queries not likely to succeed / Diane Vizine-Goetz -- The exact approach to subject searching / Diane Vizine-Goetz -- Choosing among existing subject search approaches as responses to user queries / Diane Vizine-Goetz -- Search trees for subject searching / Diane Vizine-Goetz -- The future of subject headings for online information retrieval / Diane Vizine-Goetz -- Subject authority records in the machine-readable LCSH / Diane Vizine-Goetz -- Subject information in bibliographic records / Diane Vizine-Goetz.
"Published under the auspices of OCLC Online Computer Library Center, Inc."
Includes bibliographical references and index.
Description based on print version record.
Keywords: Online bibliographic searching; Subject headings; Online library catalogs -- Subject access; Language Arts & Disciplines -- Library & Information Science -- General; Reference -- General; Automation of library & information processes; Library & information services